Evaluation of the 5S+Safety culture Policy in the Production Division at PT. RST - Alif Imam Utomo; Iwan Gusniar; Eka Yulianty (Peneliti.net, 2022)
PT. RST is a manufacturing company engaged in producing appropriate technological tools. On PT. RST has a production division which is a place for storing and managing the raw materials needed into a product. In the production division at PT. RST has implemented the 5S+Safety culture work culture policy, but at PT. RST this policy is still considered not optimal. This is because the 6S work culture that has been implemented has not been done optimally and 5S has not been optimally at the production site. So, this study aims to determine the evaluation of the application of the 6S or 6K policy carried out in the production division of PT. RST as well as to find out the process of structuring the raw materials used. Then it is necessary to manage the appropriate raw material storage function and evaluate the application of the right work culture. Therefore, the 5S + Safety culture culture needs to be more trained and suppress the application of this work culture so that the management of warehouse conditions is more stable and organized, so as to minimize the occurrence of unwanted things such as material damage, lack of storage and work accidents.